The hugs, not bullets strategy: causes and effects of crime in Mexico - Ramales Osorio , Martín Carlos (2025)
Crime in Mexico has been a persistent problem since the federal government declared a war on drug trafficking in 2006. The hugs, not bullets policy, promoted by former President Andrés Manuel López Obrador (2018-2024), attempted to address the roots of violence with a more social and less repressive approach. However, the rates of homicides, femicides, and murders of journalists reached alarming levels. The objective of this study is to investigate the causes and consequences of crime in Mexico focusing on this strategy, analyzing its impact on the reduction of violence, citizen perception of security, and the social reintegration of criminals. A mixed methodology was used, combining a hermeneutic analysis of official texts and descriptive statistics of serious crimes, collected from sources such as INEGI, SESNSP, and NGOs such as Article 19. The results show that the strategy did not reduce crime, with intentional homicide rates remaining high. feminicides and murders of journalists, and the perception of insecurity. In addition, social reintegration programs were insufficient due to a lack of resources and comprehensive approaches. As conclusion, the hugs, not bullets strategy had little effect due to problems such as poverty, marginalization and corruption.